Protean Kinematics: A Blended Model of VR Physics - Jeong, David C.; Kim, Steffie Sofia Yeonjoo; Xu, Jackie Jingyi; Miller, Lynn C. (Frontiers in Psychology, 2021)
Avatar research largely focuses on the appearance and external characteristics of avatars, but has not considered how avatar movements, and the characteristics of those movements might affect user reactions. Avatar movement represents a complex blend of inputs/outputs, physical/virtual experience, and affordances/actions. With Protean kinematics, we offer a systematic exploration into the role of movement in virtual reality (VR), and expand avatar-user appearances-based effects of the Proteus Effect to a theory of movement-based effects in affecting social perceptions (about others) and idealized perceptions (about self). We propose that the perceptual experience of VR must account for a series of hippocampal (e.g., place cells, grid cells) and entorhinal neurons (e.g., speed cells) that fire topologically in accordance to physical movement in physical space. The current work contributes to avatar embodiment with both a theoretical (typology) and methodological (physics-based measurement) approach to understanding the complex blend of physical inputs and virtual outputs that occur in VR. Offered is a novel method of distilling the blend of physical and virtual kinematics in VR to contribute to modern understandings of human-agent interaction and cognitive psychology.